1993
DOI: 10.1152/ajpcell.1993.264.6.c1538
|View full text |Cite
|
Sign up to set email alerts
|

Increases in human skeletal muscle Na(+)-K(+)-ATPase concentration with short-term training

Abstract: To investigate the effect of short-term training on Na(+)-K(+)-adenosine triphosphatase (ATPase) concentration in skeletal muscle and on plasma K+ homeostasis during exercise, 9 subjects performed cycle exercise for 2 h per day for 6 consecutive days at 65% of maximal aerobic power (VO2 max). Na(+)-K(+)-ATPase concentration determined from biopsies obtained from the vastus lateralis muscle using the [3H]ouabain-binding technique increased 13.6% (P < 0.05) as a result of the training (339 +/- 16 vs. 385 +/- 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
103
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(117 citation statements)
references
References 10 publications
14
103
0
Order By: Relevance
“…4), which may be interpreted as an adaptive mechanism in response to increased physical activity, which contributes to enhanced exercise performance (10,20,24,29,32). Several laboratories have also reported this adaptation by the Na ϩ -K ϩ -ATPase ␣ 1 -and ␣ 2 -subunits to different exercise training protocols, including strength training (10), endurance training (35), sprint training (29,32), prolonged cycle training (20), submaximal cycling exercise (22,36), 16 h of heavy intermittent cycle exercise (21), and short-term intense sprint exercise for trained soccer players (50). However, in the present study, we did not detect any statistically significant difference in the expression of the ␣ 3 -subunit of Na (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4), which may be interpreted as an adaptive mechanism in response to increased physical activity, which contributes to enhanced exercise performance (10,20,24,29,32). Several laboratories have also reported this adaptation by the Na ϩ -K ϩ -ATPase ␣ 1 -and ␣ 2 -subunits to different exercise training protocols, including strength training (10), endurance training (35), sprint training (29,32), prolonged cycle training (20), submaximal cycling exercise (22,36), 16 h of heavy intermittent cycle exercise (21), and short-term intense sprint exercise for trained soccer players (50). However, in the present study, we did not detect any statistically significant difference in the expression of the ␣ 3 -subunit of Na (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One randomized controlled trial reported increases of Na, K-pump content [21], which has been demonstrated to be low in patients with type 2 diabetes compared to healthy adults [45,46] and has been reported to increase both with endurance and sprint training in healthy individuals [47][48][49][50][51][52]. The intracellularly produced lactate leaves the cell via simple diffusion and two proteins: monocarboxylate transporter (MCT) 1 and MCT4 [53].…”
Section: Othersmentioning
confidence: 99%
“…[86] Although the greater 'fatigue resistance' of better distance athletes is not well-understood, [86,87] superior endurance performances may be related to lower rates of lactate accumulation in working muscles. [72,81,[88][89][90][91][92][93] In highly trained endurance athletes, there is little increase in plasma lactate concentration with increasing work rates [41] until exercise intensity reaches 80 to 85% of V . O 2peak .…”
Section: Effects Of Sustained High-intensity Interval Training In Welmentioning
confidence: 99%
“…O 2peak . [72,89] Part of the increase in work rates in the TT 40 rides after HIT may have resulted from a reduction in the rates of carbohydrate oxidation and lactate accumulation at the same absolute work rates after HIT. Westgarth-Taylor et al [79] showed that 12 HIT sessions decreased curvilinear rises in rates of carbohydrate oxidation and plasma lactate accumulation in successive 10-minute rides at 50, 60, 70 and 80% of the cyclists' pre-HIT W peak .…”
Section: Effects Of Sustained High-intensity Interval Training In Welmentioning
confidence: 99%